Testing for the Impact of Local Labour Market Characteristics on House Prices - Liv Osland; Inge Thorsen (European Regional Science Association (ERSA), 2006)
The starting point of this paper is a hedonic regression model where house prices are explained as a result of urban attraction and the accessibility to job opportunities in the region. The basic hypothesis is that house prices reflect that households in addition value accessibility to job opportunities in the neighborhood. We propose several measures of local labor market characteristics, and test for the impact on house prices. The alternative measures do not add considerably to the explanatory power. Still, some characteristics contribute significantly, and affect the size and interpretation of the relationship between local labor market conditions and house prices.
Keywords: 330